2016
DOI: 10.3402/jchimp.v6.32151
|View full text |Cite
|
Sign up to set email alerts
|

In the era of corona virus: health care professionals’ knowledge, attitudes, and practice of hand hygiene in Saudi primary care centers: a cross-sectional study

Abstract: BackgroundHand hygiene is one of the essential means to prevent the spread of infections. The aim of this study was to assess the knowledge, attitudes, and practice (KAP) of hand hygiene in primary care settings.MethodsA cross-sectional study using a self-reported questionnaire was conducted in primary care settings located in Riyadh, Kingdom of Saudi Arabia, under the service of King Abdulaziz Medical City (KAMC). The Institutional Review Board of KAMC Research Centre approved the study. Data were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
42
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 28 publications
13
42
1
4
Order By: Relevance
“…These ndings are in agreement with a previous study that found subjective norms and PBC had a signi cant impact on behavioral intentions [44]; [45]; [46]. In line with the ndings of Alfahan's study [47], the social norm component emerged as the most important predictor. Family members and religious leaders were important in in uencing people's intention to practice social distancing to reduce the spread of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 92%
“…These ndings are in agreement with a previous study that found subjective norms and PBC had a signi cant impact on behavioral intentions [44]; [45]; [46]. In line with the ndings of Alfahan's study [47], the social norm component emerged as the most important predictor. Family members and religious leaders were important in in uencing people's intention to practice social distancing to reduce the spread of SARS-CoV-2.…”
Section: Discussionsupporting
confidence: 92%
“…Variations in practice stemmed from personal attitudes, perceived behaviour, control and subjective norms [31], leading to the intent to wash hands. Some PCPs thought parents were knowledgeable in hand hygiene practice and therefore did not feel the need to mention hand hygiene during an RTI consultation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in view of the available national and international literature on HH, low compliance with established practices is evident, jeopardizing both user and professional safety (8,11) . In the extra-hospital environment, these data are still incipient (13)(14)(15)(16)(17)(18) . A Spanish study, carried out at PHC and in a hospital environment, found gaps in the knowledge of health professionals regarding the concept of hands hygiene and the use of alcohol solution (16) .…”
Section: Discussionmentioning
confidence: 99%
“…The achievement of this is also justified by the relevance of HCAI transmission in PHC, the rare epidemiological reports on this population (5) , the acknowledged deficit of adherence to StanP and SpeP by health professionals in general (11) , the difficulty of comparison between the results of the few recent studies in this care setting (12)(13)(14)(15)(16) and the limited availability of assessment tools (17)(18) , which have not yet been validated.…”
Section: Introductionmentioning
confidence: 99%